21st century teaching and learning methods towards secondary school students’ satisfaction and their academic performance / Nur Hazirah Azahar, Norshafiqah Mohd Noryatim and Siti Zuraihan Najian Mohd Zahid - Azahar, Nur Hazirah; Mohd Noryatim, Norshafiqah; Mohd Zahid, Siti Zuraihan Najian (2017)
21st century teaching and learning method is introduced by the Ministries of Malaysian Education, as a way to improve the student’s motivation in becoming more proactive students. The traditional method that was used by the schools was mostly exam – oriented and especially for the under–achiever students, who cannot survive this traditional method as there were a lot of unpractical method involved, it will affect their academic achievement negatively. Since then, some schools has applied the 21st century teaching and learning method to prevent that problems happen to the future generation of leaders. In spite of that, using multiple cross–sectional case study research, the study is conducted to know whether there is a difference in students’ academic performances between schools that applied 21st century method (case), compared with the other schools that still applied teacher–centered methods (control), and whether there is a difference between the students’ satisfaction towards their current teachings between both schools. The data were collected from Sekolah Menengah Kebangsaan (SMK) Kampung Chengal (case, n=36) and Sekolah Menengah Kebangsaan (SMK) Pintu Geng (control, n=36).The results were compared and shown that there is a significantly different in students’ academic performance (p<0.000) and also in the students’ satisfaction (p<0.000) between SMK Kampung Chengal and SMK Pintu Geng. The results indicate that there is a positive significant impact of implementing the 21st century method. Therefore, this method is recommended to be continuously applied for a long time